Lewis & Clark : blazing a trail west - Burrows, John, 1972- (Sterling, 2008)
Describes the journey taken by William Clark and Meriwether Lewis after leaving Illinois in 1804 to explore the unknown western region of North America where they discovered animals, and landforms, and interacted with several Native American tribes.